2021
DOI: 10.1186/s40575-021-00103-4
|View full text |Cite
|
Sign up to set email alerts
|

Genetics of canine subvalvular aortic stenosis (SAS)

Abstract: Subvalvular aortic stenosis (SAS) is one of the most common congenital heart defects of dogs. The disease is characterized by obstruction of the left ventricular outflow tract, resulting in pressure overload on the left ventricle. The etiology of obstruction is a fibromuscular nodule, ridge, or ring of tissue that increases aortic outflow tract velocity. This review is focused on the prevalence, inheritance pattern, and current genetic insights of canine SAS. The prevalence of this disease was reported at 4.7 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
4
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 36 publications
0
4
0
1
Order By: Relevance
“…Six dogs had underlying congenital heart disease (SAS) which has been previously suggested to predispose dogs to IE due to creating turbulent blood flow and damage to the aortic cusps (MacDonald 2010 ). In addition, SAS is one of the most common congenital heart conditions in large breed dogs which may account for their predisposition to IE (Ontiveros & Stern 2021 ). Male dogs have also been shown to be predisposed to SAS which may also partly explain their higher prevalence (Schrope 2015 ).…”
Section: Discussionmentioning
confidence: 99%
“…Six dogs had underlying congenital heart disease (SAS) which has been previously suggested to predispose dogs to IE due to creating turbulent blood flow and damage to the aortic cusps (MacDonald 2010 ). In addition, SAS is one of the most common congenital heart conditions in large breed dogs which may account for their predisposition to IE (Ontiveros & Stern 2021 ). Male dogs have also been shown to be predisposed to SAS which may also partly explain their higher prevalence (Schrope 2015 ).…”
Section: Discussionmentioning
confidence: 99%
“…Die Aortenstenose ist die häufigste angeborene Herzpathologie bei großen Hunden und kommt selten bei der Katze vor 10 , 51 . Die Verengung der Aorta führt zu einer verminderten Ausflussfähigkeit des linken Ventrikels.…”
Section: Aorten- Und Pulmonalstenoseunclassified
“…Therefore, the current most commonly employed treatment for SAS in dogs is pharmacological. A beta-adrenergic blocker serves to lower a patient’s heart rate and increase myocardial perfusion; atenolol, which is cardio-selective, tends to be the beta-blocker of choice [ 42 , 62 - 64 ]. Treatment is generally selected for dogs with moderate to severe forms of SAS, as mild cases do not often exhibit symptom development or significant lifespan alterations.…”
Section: Clinical Treatmentmentioning
confidence: 99%
“…Their studies implicate a polygenic mode of inheritance or an autosomal dominant mode of inheritance (possibly with modifiers). These continue to be the leading hypothesized modes of inheritance; additional information is required to more definitively support or refute these contradicting hypotheses [ 5 , 6 , 64 ]. Furthermore, their results suggested that the trait may not have complete specificity, for some crosses between affected individuals yielded offspring with valvular and subvalvular pulmonic stenosis in addition to SAS [ 5 ].…”
Section: Genetics Vs Environment Mode Of Inheritance and Variant Disc...mentioning
confidence: 99%
See 1 more Smart Citation